Sakura and the new boy - Weinberger, Kimberly; Giles, Kathleen Woodward, Meredith (Scholastic New York, 2001)
A mysterious boy named Lee joins Sakura's class. He seems to possess the same kind of magic that she does. He, too, is a cardcaptor, but is he a friend or foe? Illustrations